Investigating the effect of the shadow economy on Malaysia’s economic growth: Insight from a nonlinear perspective - Gamal, Awadh Ahmed Mohammed; Salem, Sultan Ali Mohammed; David, Joseph; Tha, Gan Pei; Viswanathan, K Kuperan (Asian Economic and Financial Review, 2025)
Utilizing a nonlinear autoregressive distributed lag (NARDL) model, the goal of this study is to find out if the shadow economy’s (SE) effect on Malaysia’s economic growth is not linear from 1970 to 2022. This model uniquely identifies potential nonlinearities or asymmetries in the relationship between SE and growth. The results of the bounds tests show that there is a strong long-term link between economic growth and both good and bad changes in the SE, as well as variables like inflation, urban population growth in cities, financial development, and economic uncertainty. Furthermore, the results indicate that the SE’s influence on growth is nonlinear, both in the short and long term. In particular, both growing and shrinking the SE have positive effects on growth, but growing the SE has a bigger long-term effect than shrinking it. Conversely, in the short term, reductions in the SE’s size have a greater impact. Additionally, inflation, urban population growth, financial development, and economic uncertainties emerge as key determinants of growth across both time horizons. These findings suggest the need for policies that reduce the size of the shadow economy and encourage the shift from informal to formal economic activities to foster sustained economic growth.